STUDI ANALISA KEBUTUHAN RUANG PARKIR POLITEKNIK NEGERI SRIWIJAYA - Wahidin Wahidin (Politeknik Negeri Sriwijaya, 2014)
Parking is an essential part of an infrastructure building. It should be available on a building which is utilized as the activity centre. As the central activity of D3 education with the number of more than 4,000 students, the parking area of State Polytechnic of Sriwijaya needs concern. Furthermore,it needs a research. The purpose of the research is to find out available facility based on its allocation, to obtain the parking characteristics, to utilize available area, to predict parking needs within 5 years ahead and to recommend the parking development. The writer conducted the observation for several days on lectures time activity. It was conducted by watching the traffict flow around the State Polytechnic campus. The result of analysis showed that the parking accumulation for motorcycle and four- wheel vehicle was 2,018 and 198. The allocation of available parking area was 2,100 m2 for motorcycle and 3,710 m2 for four-wheel vehicle. Furthermore, based on optimation, it was found that the surface of parking area for motorcycle was 5,621.26 m2. The writer also found that the parking area surface based on its allocation for four- wheel vehicle, was 3,710 m2. Based on facts above, the writer suggests that for the smoothness of traffic flow inside the State Polytechnic campus, the parking area need to be completed by functional road signs.